OPTIMIZATION OF THE FEASIBILITY OF MICRO HYDRO POWER PLANT (PLTMH) RAMPUSA SUB DISTRICT OF LEMBANG REGENCY PINRANG - Sirad, Mochammad Apriyadi Hadi; Aminuddin, Rosihan (Department of Electrical Engineering, University of Patria Artha, 2017)
Economic growth and basic electrical energy pentarifan (TDL) that is determined by the Government and PLN is the thing that most affect the usage/consumption of electrical energy, as in the theory of microeconomics, the demand for a commodity including energy electricity is influenced by various factors, including the following: the requested prices of goods, the prices of other goods, income, tastes and prosperity. The provision of electricity is not only meant as a tool for tackling poverty, but also dimaksdukan for equitable development and advance the villages as a force for the national economy. Therefore to meet the need for electric lighting for remote areas need to be created a tool that can reach remote places that are cheap and environmentally friendly, that micro hydro power plant. This research aims to know the feasibility of Micro Hydro power plant Rampusa sub district of Lembang Regency pinrang. This research is the research of ex-post-facto that is descriptive. The sample in this research is to look at the technical aspects of PLTMH. As for side input consists of water discharge (Q) effective falls high (H), the State of the generator, turbine, form the type of pipeline and the turbine House (power house). As for the Power output is generated (P), Village PLTMH rampusadan load Protection installed.The result of the research of the optimization of the feasibility of Micro Hydro power plant Rampusa sub district of Lembang Regency Pinrang, with discharge water 0.17 m3/sec, 23 m high waterfall with a power generator with a capacity of kW 26.04 20 kVA, kVA 32.55 should use by using different types of crossflow turbine the turbine type France should use, type of PVC pipe 12